Flight Test Evaluation for Tilt Rotor Unmanned Aerial Vehicle Development - A A Arif; R A Sasongko (AVIA, 2021)
Tiltrotor Unmanned Aerial Vehicle (UAV) is type of UAV that combine fixed wing (FW) and multirotor (VTOL) configuration in order to be able to perform instant transition from one configuration to another. Tiltrotor UAV has advantage to perform takeoff and landing from limited space such as plantation farm, forest, and residential area. Tiltrotor also can carry various mission since it has 2 configuration such as cargo drone, safer payload dropping, and mapping. In this research tiltrotor UAV designed with ruddervator (V-Tail) configuration with 3 motors in total, 2 motors placed on main wing with tilting capability and 1 motor placed at the end of fuselage as pitch controller in VTOL mode. Test flight will be conducted and evaluated to test UAV capability in hovering and transition from one mode to another